A Consecutive Four‐Component Synthesis of Polysubstituted Thiophenes in Aqueous Medium. Issue 23 (14th June 2018) - Adib, Mehdi; Rajai‐Daryasarei, Saideh; Pashazadeh, Rahim; Jahani, Mehdi; Yazzaf, Rozita; Amanlou, Massoud
Abstract : An efficient and straightforward four‐component synthesis of mono‐, bi‐ and tricyclic thiophenes from C–C + C + C + S atom fragments from 1, 3‐dicarbonyl compounds, aldehydes, activated methylene halides and elemental sulfur in aqueous medium is described. Arylidene‐1, 3‐dicarbonyls, N ‐phenacylpyridinium bromides/ N ‐( p ‐nitrobenzyl)pyridinium chloride, pyridinium ylides and 2, 3‐dihydrofurans are believed to be the key intermediates of these consecutive transformations. This synthetic strategy provides a potential route to the construction of a library of highly substituted thiophenes with a large substrate scope in good‐to‐excellent yields. Abstract : An efficient and straightforward four‐component domino synthesis of mono‐, bi‐ and tricyclic thiophenes from 1, 3‐dicarbonyl compounds, aldehydes, activated methylene halides and elemental sulfur in aqueous medium is described.